2008
DOI: 10.1016/j.euroneuro.2008.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Differences in regional blood volume during a 28-day period of abstinence in chronic cannabis smokers

Abstract: Cerebral blood volume (CBV) studies have provided important insight into the effects of illicit substances such as cannabis. The present study examined changes in regional blood volume in the frontal and temporal lobe, and the cerebellum during 28 days of supervised abstinence from cannabis. Dynamic susceptibility contrast MRI (DSCMRI) data were collected on 15 current, long-term cannabis users between 6 and 36 hours after the subjects' last reported cannabis use (Day 0), and again after 7 and 28 days of absti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana. However, CB1 receptors in cerebellum are also expressed in neurons and glia (58), and the cerebellum is a region that is affected in marijuana abusers (59)(60)(61); thus, we cannot rule out the possibility that other factors contribute to the lack of an effect of MP on the cerebellar DV in the marijuana abusers.…”
Section: Mp-induced Changes In DVmentioning
confidence: 98%
“…Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana. However, CB1 receptors in cerebellum are also expressed in neurons and glia (58), and the cerebellum is a region that is affected in marijuana abusers (59)(60)(61); thus, we cannot rule out the possibility that other factors contribute to the lack of an effect of MP on the cerebellar DV in the marijuana abusers.…”
Section: Mp-induced Changes In DVmentioning
confidence: 98%
“…The imaging methods used were 133 Xe-SPECT (Mathew et al 1986 ;Tunving et al 1986 ;Lundqvist et al 2001 Sneider et al 2008). In a group of nine chronic cannabis users, assessed within 1 week of drug cessation, Tunving et al (1986) found a reduction in global CBF relative to controls that did not correlate with the duration of cannabis consumption.…”
Section: Non-acute Effects On Resting State Activitymentioning
confidence: 99%
“…Mathew et al (1986) assessed 17 chronic cannabis users after 12 h of abstinence and found no differences in either global or rCBF between cannabis users and controls. Sneider et al (2008) examined changes in regional blood volume (rCBV) in a group of 17 healthy controls and 15 cannabis users. Imaging data were collected between 6 and 36 h after the subjects' last cannabis use, and again after 7 and 28 days of supervised cannabis abstinence.…”
Section: Non-acute Effects On Resting State Activitymentioning
confidence: 99%
“…Similarly, looking beyond MS, the resting-state functional imaging literature gives few clues as well. Of the 6 resting-state studies that explored the nonacute effects of cannabis, only one used fMRI 24 and here the emphasis was on cerebral blood volume as elicited by dynamic susceptibility contrast MRI. Serial data were collected during an enforced period of abstinence from cannabis users and healthy, nondrugusing control subjects.…”
Section: E14mentioning
confidence: 99%